Timed regulation of P‐element‐induced wimpy testis–interacting RNA expression during rat liver regeneration. Issue 3 (1st July 2014) - Rizzo, Francesca; Hashim, Adnan; Marchese, Giovanna; Ravo, Maria; Tarallo, Roberta; Nassa, Giovanni; Giurato, Giorgio; Rinaldi, Antonio; Cordella, Angela; Persico, Marcello; Sulas, Pia; Perra, Andrea; et al.
<x xml:space="preserve">Abstract</x> Small noncoding RNAs comprise a growing family of molecules that regulate key cellular processes, including messenger RNA (mRNA) degradation, translational repression, and transcriptional gene silencing. P‐element‐induced wimpy testis (PIWI)‐interacting RNAs (piRNAs) represent a class of small RNAs initially identified in the germline of a variety of species, where they contribute to maintenance of genome stability, and recently found expressed also in stem and somatic cells, where their role and responsiveness to physiopathological signals remain elusive. Here, we investigated piRNA expression in rat liver and its response to the stimuli exerted by regenerative proliferation of this organ. Quantitative polymerase chain reaction analysis identify in the liver the RNAs encoding PIWIL2/HILI, PIWIL4/HIWI2, and other components of the piRNA biogenesis pathways, suggesting that this is indeed functional. RNA sequencing before, during, and after the wave of cell proliferation that follows partial hepatectomy (PH) identified ∼1, 400 mammalian germline piRNAs expressed in rat liver, including 72 showing timed changes in expression 24‐48 hours post‐PH, a timing that corresponds to cell transition through the S phase, returning to basal levels by 168 hours, when organ regeneration is completed and hepatocytes reach quiescence. Conclusion: The piRNA pathway is active in somatic cells of the liver and is subject to regulation during the pathophysiological process of organ regeneration, when these molecules are available to exert their regulatory functions on the cell genome and transcriptome, as demonstrated by the identification of several liver mRNAs representing candidate targets of these regulatory RNAs. (Hepatology 2014;60:798–806)